Continuity within a community integrated palliative care model and the influence of remote and digital approaches to care: a qualitative interview study - Emma Ladds; Malaika Ivey; Katrina Gadsby; Elin Preest; Ffion Samuels; Victoria Bradley (BJGP Open)
Background: Demand for palliative care is rising. Recent UK policy approaches promote integrated care models — collaborations between GPs and multidisciplinary specialists — and remote and digital practices. The extent to which different forms of continuity are supported within this evolving context is currently unclear. Aim: To explore the experience of continuity and impact of remote and digital practices within an integrated palliative care model. Design & setting: A qualitative interview study of patients and bereaved relatives recruited from a GP practice list and healthcare professionals delivering the integrated palliative care service for that population. Method: Twenty narrative and semi-structured interviews were conducted with 22 patients, relatives, and professionals between May 2022 and November 2023. They explored how care was delivered or received, focusing on coherency and the use of remote and digital practices. Data were theorised using a novel framework that considered psychodynamic, biomedical, sociotechnical, and sociopolitical domains of continuity. Results: The need for human care and connection were of primary importance and affected by intersubjective, biomedical, sociotechnical, and sociopolitical factors that influenced continuity of care. Despite the logistical ease of remote and digital practices, professionals had to work harder or around technologies to provide a ‘caring’ service. This was exacerbated by a lack of co-localisation, loss of longitudinal relationships, and reduction in tacit knowledge. Conclusion: Numerous complex factors and the exacerbating effects of remote and digital practices influence continuity and coherency within an integrated palliative care model.